PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK ELEKTRONIK BERBASIS PREDICT, OBSERVE, AND EXPLAIN - Anisa, Husna; Yusri, Radhya; Mardiyah, Ainil (Jurnal Riset Pembelajaran Matematika, 2024)
This research aims to produce valid and practical E-LKPD on SPLTV material. This research is a type of research and development (R&D) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects of this research were class X students of SMAN 1 Lembah Gumanti. The instruments used in this research were validation questionnaires and practicality test questionnaires. The results of the research can be concluded that the E-LKPD based on POE (Predict, Observe and Explain) in Class X Variable Linear Equation Systems Material at SMAN 1 Lembah Gumanti is declared valid and practical for use by educators and students